Conducting Narrative Studies in Pakistan: Reflections from the Field - Haji Karim Khan (Journal of Education and Educational Development, 2020)
This reflective paper emerges from the analysis of my experience of carrying out narrative studies in Pakistan — a country where narrative research in education is still very young. Field-notes, reflective journals and research memos were the key sources for the analysis. The reflections showcase my experiences of getting the insider’s views, co-constructing narratives, and co-constructing the research reality while carrying out narrative research studies in Pakistan. Findings have pertinent implications for narrative research studies in Pakistan and elsewhere in a similar settings.